TEACHERS' KNOWLEDGE, ATTITUDES AND PRACTICES TOWARD EPILEPSY IN TARKWA-NSUAEM MUNICIPALITY - AHMED, KHALID SALIM; ASARE, RICHARD OPOKU; BOAKYE-YIADOM, AKWASI; ARYEE, PAUL ARMAH (European Journal of Health Sciences, 2020)
Purpose: The objective of this study was to assess the knowledge, attitudes and practices of basic school teachers on epilepsy in Tarkwa-Nsuaem Municipality. Methodology: The study employed a descriptive cross-sectional design. Teachers were sampled from public basic schools in the municipality using the Yamane's formula for known sampling frame to arrive at 226 participants for the study. The multi-stage and convenience sampling techniques were then used to sample teachers from five of the seven circuits with each circuit being allocated 62 teachers for the study. A semi-structured questionnaire which was used for the data collection was adapted from a study in Namibia. Chi squares and P-values were applied to determine the association between dependent and independent variables as confidence level set at 0.05. Data was analyzed with SPSS version 20. Results: The study found that majority of the teachers, 167 (73.9%) were knowledgeable about epilepsy and 191 (84.5%) had positive attitudes toward epilepsy. However, seizure management practices among the teachers were poor; only 44 (19.3%) of the teachers had appropriate seizure management practices. Notwithstanding, the religion of the teachers was found to be significantly associated with knowledge on epilepsy (p=0.041). The study found that marital status had an effect on attitudes toward epilepsy (p=0.004), whilst educational qualification was also significantly associated with attitudes toward epilepsy (p=0.001). The self-rated knowledge levels of the teachers, had no significant relationship with seizure management practices (p=0.508). Conclusion: Though majority of the teachers had adequate knowledge and positive attitudes toward epilepsy, it did not reflect in appropriate management of seizure. Recommendation: The Ghana Health Service should collaborate with the Ghana Education Service in training teachers on the management of seizure attacks.